Pendidikan dalam Perspektif Islam - Asrori Asrori (Hikmah: Journal of Islamic Studies, 2017)
Sinceitsbirth,Islamisareligionthathasconcernedoneducation.The firstverseofAl-Qur’anfortheProphetMuhammadandtheprophetic missionofMuhammadshowthisconcern.Theconditionofignorance that dominated the Arab society in the past was tried to be changed by Islam. The Islamic education is often called tarbiyah and ta’lim al-tarbiyah which means education that includes aspects of science and morality. Therefore, Islamic education is to cultivate humans’ minds and to regulate humans’ characters and attitudes based on the Islamic teachings. Meanwhile al-ta’lim in Islamic education means teaching, which only gives knowledge to the students. According to Islamic teachings, humans have two potentials (evil and piety). The teachings of Islam acknowledge the differences of people’s talents but the differences do not mean that they cannot be formed at all. In order to achieve the goals well, education needs to be adapted with the development of thestudents. Keywords: Islam, education, tarbiyah, and ta’lim. Sejak kemunculannya, Islam adalah agama yang konsen dengan pendidikan. Ayatyangpertamaturundanmisikenabian Muhammad menunjukkan hal tersebut. Kondisi kebodohan yang mendominasi masyarakat Arab pada waktu itu berusaha untuk dirubah oleh Islam. Pendidikan Islam sering diistilahkan dengan tarbiyah dan ta’lim al-tarbiyah yang berarti pendidikan yang mencakup aspek ilmu dan akhlak. Oleh karena itu, pendidikan menurut Islam ialah menumbuhkan pikiran manusia, serta mengatur akhlak dan perangainya berdasarkan ajaran Islam. Sedangkan al-ta'lim dalam dunia pendidikan berarti pengajaran, yang hanya memberikan ilmu semata kepada anak didik. Menurut ajaran Islam, manusia itu mempunyai dua potensi (jahat dan takwa atau positif). Ajaran Islam mengakuiadanyaperbedaanbakatpembawaanpadadiriseseorang, namun perbedaan tersebut bukan berarti tidak bisa dibentuksama sekali.Agarmencapaisasarandanberhasildenganbaik,pendidikan perlu disesuaikan dengan perkembangan anak didik. Kata kunci: Islam, pendidikan, tarbiyah, ta’lim